Influence of high hydrostatic pressure on quality parameters and structural properties of aloe vera gel (Aloe barbadensis Miller) - Vega-Gálvez, Antonio (Springer India, 2012)
The aim of this work was to study the effect of high hydrostatic pressure (HHP) on colour, dietary fibre, vitamin C content, polysaccharides content, physico-chemical and structural properties of aloe vera gel at three pressure levels (300, 400 and 500 MPa for 3 min) after 35 days of storage at 4 ± 1 °C. The results showed that HHP exerted a clear influence on most of the quality parameters studied. Moisture, protein and fat contents did not show changes with an increasing pressure. Ash, crude fibre and carbohydrates content increased with increasing pressure. Vitamin C content did not show significant differences after 35 days of storage. The variation of colour in the samples increased at 500 MPa. Total dietary fibre, water holding capacity and firmness increased with pressure. However, all HHP-treated samples presented a decrease in hydration ratio and polysaccharides content; and also minor alterations in the structural properties were produced at HHP of 300–500 MPa, resulting in a high quality gel.